Analysis of ANRIL gene polymorphism rs4977574 association with kidney cancer development in Ukrainian population. - A. D. Volkogon; V. Yu. Harbuzova; A. V. Ataman (Medičnì Perspektivi)
ANRIL (Antisense Non-coding RNA in the INK4 Locus, also known as CDKN2B-AS1) – 3.8-kb long non-coding RNA transcribed from the antisense strand of INK4b-ARF-INK4a gene cluster. It is known that ANRIL overexpression is associated with development of oncological pathologies of different localization. In addition, there are a number of studies devoted to role of ANRIL genetic polymorphism in emergence and progression of tumors, including tumors of genitourinary system. The aim of the study was to check the possible association between ANRIL gene polymorphism rs4977574 and kidney cancer development in representatives of Ukrainian population. Whole venous blood of 101 patients with clear cell renal cell carcinoma (CCRCC) (42 women and 59 men) and 100 patients without oncology history (34 women and 66 men) was used in the study. DNA from blood white cells was extracted using GeneJET Whole Blood Genomic DNA Purification Mini Kit (Thermo Fisher Scientific, USA). Genotyping of rs4977574 ANRIL gene polymorphic locus was performed using real-time polymerase chain reaction (real-time PCR) method in the presence of TaqMan assay C_31720978_30. The mathematical data were processed using the SPSS software package (version 17.0). P values <0.05 were considered as statistically significant. It was found that difference in rs4977574-genotype distribution between patients with CCRCC and control persons was absent in general group (P=0.216). At the same time, the statistical analysis stratified by gender showed that both in female and male subjects rs4977574-genotypes frequency also did not differ significantly between comparison groups (P=0.526 and P=0.160, respectively). However, after adjusting for age, body mass index, and smoking habits statistically significant association between rs4977574 ANRIL gene polymorphism and risk of kidney cancer development was detected in male subjects under superdominant inheritance model (P=0.049). It was revealed that heterozygotes (AG-genotype) have 2.17-fold  higher risk of CCRCC development (95% CI=1.005-4.695) compared to patients with AA- and GG-genotypes. In summary, this is the first report about ANRIL gene polymorphisms association with kidney cancer. Obtained results revealed that rs4977574 is related to kidney cancer risk only in Ukrainian men. Male individuals with AG-genotype have higher risk of CCRCC development compared to AA- and GG-genotypes carriers.